Decrypting the real life escape room experience - Lim, Qian Pink; Mohd Ridzuan, Darun; Nawanir, Gusman (KnE Social Sciences, 2019)
An escape room is a game that requires a group of players to solve a variety of tasks within a given amount of time in order to fulfill a specific goal, typically escaping a locked room. Despite gaining tremendous popularity of the game in Malaysia, there is no study being conducted in this area. Existing customer experience frameworks offer a limited explanation of this rising phenomena due to the unique inherent nature of Escape Room. Towards this end, the present paper aims to identify the key constructs of Malaysian Escape Room customer experience and determinants of the players revisit intention with respect to the Escape Room. The research is conducted on 20 players who have played at least one game in any Escape Room establishment in Malaysia. This study adopts the sequential incident technique, a qualitative approach to unearth the hidden perception of players. Thematic analysis was subsequently used to analyse the data which revealed fifteen determinants of which 9 are related to the model of goal-directed behaviour. Our research contributes to the body of knowledge in mapping customer experience in this fair nascent industry. Insights from this study are aimed at benefiting Malaysian Escape Room business operators in designing and enhancing the customer experience in their escape rooms.